2021
DOI: 10.3389/fmicb.2021.628503
|View full text |Cite
|
Sign up to set email alerts
|

Increased Organic Fertilizer and Reduced Chemical Fertilizer Increased Fungal Diversity and the Abundance of Beneficial Fungi on the Grape Berry Surface in Arid Areas

Abstract: Fertilizer practices can significantly impact the fruit quality and microbial diversity of the orchards. The fungi on the surface of fruits are essential for fruit storability and safety. However, it is not clear whether fertilization affects the fungal diversity and community structure on the surface of grape berries. Here, grape quality and the fungal diversity on the surface of grapes harvested from three fertilizer treatments were analyzed shortly after grape picking (T0) and following 8 days of storage (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 77 publications
(92 reference statements)
1
3
0
Order By: Relevance
“…These findings indicate that CFOF improved the soil microbial community structure in a manner that was relative to the organic matter, humic acid, and amino acids and which could increase soil microbial activity. These results are similar to the research of previous study [46,47]. Moreover, the study showed that soil microbe properties were the largest in July and were related to local temperature and humidity [48].…”
Section: Discussionsupporting
confidence: 91%
“…These findings indicate that CFOF improved the soil microbial community structure in a manner that was relative to the organic matter, humic acid, and amino acids and which could increase soil microbial activity. These results are similar to the research of previous study [46,47]. Moreover, the study showed that soil microbe properties were the largest in July and were related to local temperature and humidity [48].…”
Section: Discussionsupporting
confidence: 91%
“…The nutrient content of chemical fertilizers is higher than that of organic fertilizers, but it can easily cause soil degradation and environmental pollution. Several studies have found substantive evidence to show that combining chemical and organic fertilizers can improve the quality of a variety of fruits ( Wu et al, 2021a ). Caris-Veyrat et al (2004) reported that the levels of carotenoids, polyphenols, and vitamin C were higher in organically cultivated tomatoes than in traditional agricultural tomatoes.…”
Section: Introductionmentioning
confidence: 99%
“…Under organic fertilisation management, enhanced soil nutrient availability [24] and improved soil quality [25] have been reported. In addition, Wu et al [26] suggested that using organic nutrient sources can be an effective practice to restore microbial biomass loss due to the intensive application of chemical fertilizers. Finally, they can play a positive part in climate change mitigation by soil carbon sequestration [24].…”
Section: Introductionmentioning
confidence: 99%